(untitled) (Tempo e Argumento, 2018)
This article discusses the development of oral history in the United States and how this has led the field to becoming interdisciplinary in interesting and useful ways. It traces its origins in the 17th century and explains its establishment as method (oral data collection), a subfield of history (oral historiography) and a resource for teachers, communities, and researchers of all kinds (oral history). The author describes the practical applications of oral history in other fields such as anthropology, education/ teaching, ethnic studies/ethnohistory/American studies, folklore, gerontology, legal studies, literary history, media studies and media production, and women and gender studies. A review of oral history guides is also given. The article ends with an update on how oral historians are coping with the new, anti-intellectual orientation of President Trump and his right-wing agenda. Keywords: Oral History. USA. Oral Data Collection. History-Telling.